(untitled) (Journal of Asian Development Studies, 2024)
This cross-sectional study aimed to evaluate the knowledge, attitudes and practices of secondary school students regarding carbonated drinks in the district of Rahim Yar Khan, Punjab, Pakistan. This study was conducted through a self-reported questionnaire, and 350 students participated in the survey from rural (n=148; 42.29%) and urban areas (n=202; 57.71%). 77.02% of rural students and 84.65% of urban students were aware of carbonated drinks. 31.08% of rural and 44.05% of urban students were mindful of carbonated drinks’ components (p=0.014). 16.89% of rural students and 81.76% of urban students were known to know the caloric values of carbonated drinks (p<0.001). 89.19% of rural and 96.04% of urban students were aware of sugar-free carbonated drinks (p=0.012). 85.81% of rural students and 76.73% of urban students believed that consuming carbonated drinks is bad forhealth (p=0.034). 66.89 %, 11.49%, 34.46% 70.95% &68.92% rural students and 82.18%, 40.09%, 29.21%, 84.16% & 83.17% urban students thought that carbonated drinks had association with obesity (p=0.001), bone decay (<0.001), dental caries (p=0.296), belching (p=0.003) and hyperacidity (p=0.002) respectively. 66.89% & 75.68% of rural students and 74.25% & 79.21% of urban students believed that carbonated drinks were associated with diabetes type II and sleep disturbance, respectively. 64.19% of rural and 71.78% of urban respondents showed positive attitudes and agreed to stop consuming soft drinks. Most secondary school students from both areas preferred to drink carbonated soft drinks even with their awareness of the health issues of these drinks. Potential repercussions from the authorities in charge of thegovernment might raise people’s awareness of the problem.